Entrepreneurship in Brazil: the role of human, psychological, and social capital in entrepreneurial success - Correia, Maria Ana Barros (2021)
The role of entrepreneurship as a social, economic, and financial endorser for the disadvantaged brackets of societies brings a new perspective on entrepreneurship as a booster of equality. However, in country contexts like the Brazilian one, it is often privileged individuals who possess the resources to engage in successful entrepreneurial behaviour. The structural issues of the Brazilian entrepreneurial ecosystem put the different types of capitals into evidence as factors that may hinder or foster entrepreneurial success. The aim of this paper is, therefore, to investigate how the financial position of an individual in society may affect his access to human, psychological, and social capital, and how the access to these capital dimensions may affect, consequently, the success of this individual as an entrepreneur. A quantitative mediation model was applied to analyse the effect of income on capital and, consequently, on entrepreneurial success for a dataset of Brazilian entrepreneurs. Results demonstrate the existence of a positive relationship between income, psychological capital, and entrepreneurial success, meaning that the individual income of individuals positively affects their psychological capital and, consequently, their entrepreneurial success. Despite the existence of a positive statistically significant relationship between income and human capital, no significance relationship was recognized between the variables of income and social capital, nor human or social capital with entrepreneurial success.